LIGHT ENVIRONMENT AND PHOTOSYNTHESIS OF AN UNDERSTORE AND A PIONNER SPECIES FROM PREMONTANE RAINFOREST OF COSTA RlCA - Stegemann, Jens (Universidad de Costa Rica, Sede de Occidente, 2012)
Light environments of gap and understorey microsites were examined in a premontane wet forest area at the Reserva Biológica Alberto M1. Brenes (RBAB), 40 km NW of San Ramón, Alajuela, Costa Rica. The light conditions varied both, in spatial and temporal pattems. Understorey sites were characterized by a low dimlight background (1 5-1 8 p o l m-2s-' ) occasionally interrupted by short lightfletcks of direct irradiante ( 4 0 0 pmol m-2s-' ).